From certificates to comprehensive records: innovating with UiTM Kedah Student Activity Transcripts (UiTMKDH SAT) - Othman, Muhammad Hanif; Rabun, Mohd Nazir; Mohd Amin, Mohd Hamidi Adha (Universiti Teknologi MARA, Kedah, 2023)
Universities have a broader role encompassing more than just academic progress; they also contribute to the overall development of students, including non-academic aspects. In this context, UiTM Kedah recognizes the significance of fostering diversified student engagement. Therefore, to address this issue, this study is aims to propose and implement the UiTM Kedah Student Activity Transcript (UiTMKDH SAT) as a comprehensive transcript, similar to an academic transcript, encompassing students' extracurricular, intracurricular, and co-curricular involvements. Students will obtain Co-Curricular Activity Cumulative Point (CACP) for each activity they participate to recognize their holistic development. This establishment of a merit-based system closely tied to their active involvement functions as a motivational catalyst, encouraging students to heighten their engagement in extracurricular activities. This strategic alignment amplifies their commitment, paralleling their dedication evident in academic accomplishments as reflected in their academic records. The implementation of the UiTMKDH SAT yields transformative benefits for students. It alleviates the need for students to manage numerous certificates for various activities, replacing this complex documentation process with a efficient approach. When students seek employment opportunities, the UiTMKDH SAT can be conveniently presented, simplifying the application process. This transition from certificates to the UiTMKDH SAT aligns with contemporary strategies, optimizing efficiency during job searches. Moreover, employers gain insights into students' competencies and involvements, enhancing their understanding of potential candidates.